1990
DOI: 10.1192/pb.14.10.611
|View full text |Cite
|
Sign up to set email alerts
|

Future child and adolescent psychiatrists: a further survey of senior registrar training

Abstract: Child and adolescent psychiatry is a growing speciality. Significant increases in workload, the reasons for which have been described elsewhere (Black, 1989), have led to an expansion in consultant posts across the UK. Recently the Joint Planning and Advisory Committee (JPAC) reviewed senior registrar numbers and recommended an increase in the establishment by 38 whole-time equivalents in England and Wales, a rise of 38%, to meet the expected shortfall. How existing senior registrars, as well as this large num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…oneto-one weekly meetings, regularly timetabled and of at least one hour's duration, follows so closely that proposed by the JCHPT guidelines. Despite this, the study confirms the findings of Boots & Cottrell (1990) that 10 to 20% of trainees have supervision experiences which do not meet these criteria. In contrast, there was considerable dis parity between ideal and practice on the issue of regular review of cases.…”
Section: Commentsupporting
confidence: 81%
See 1 more Smart Citation
“…oneto-one weekly meetings, regularly timetabled and of at least one hour's duration, follows so closely that proposed by the JCHPT guidelines. Despite this, the study confirms the findings of Boots & Cottrell (1990) that 10 to 20% of trainees have supervision experiences which do not meet these criteria. In contrast, there was considerable dis parity between ideal and practice on the issue of regular review of cases.…”
Section: Commentsupporting
confidence: 81%
“…A system of regular inspection of training schemes identifies the extent to which these are met. Bools Si Cottrell (1990) presented results of a survey of higher trainees in child and adolescent psychiatry which suggested that changes in training and in trainees' attitudes when com pared to an earlier survey in 1979 [Garralda et al, 1983] had broadly followed JCHPT guidelines. The committee can therefore be seen to function as an important link in an interactive process of training and educational development.…”
mentioning
confidence: 99%
“…Surveys of trainees' attitudes to training matters employing question naires have already provided useful information for planning purposes (Garralda et al, 1980 andBools & Cottrell, 1990). This type of approach has the benefit of being easy to organise and is well supported judging by the response to this study.…”
Section: Resultsmentioning
confidence: 60%
“…In 1979, a postal questionnaire was sent to all 107 senior registrars in training (Garralda et al, 1983). In 1988, following a revision of training guidelines a further questionnaire survey was conducted (Bools & Cottrell, 1990). Given the major changes in higher training since this last survey, it seemed timely to conduct another survey.…”
Section: Discussionmentioning
confidence: 99%